2003
DOI: 10.1118/1.1563663
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculated correction factors for primary standards of air kerma

Abstract: Many laboratories with cavity chambers as primary standards for air kerma are considering using additional Monte Carlo calculated correction factors, in particular the correction for attenuation and scatter in the walls, Kwall, and possibly the correction for point of measurement, Kan. Standards labs also use Monte Carlo calculated Spencer-Attix stopping-power ratios for graphite to air. The purpose of this article is to investigate the sensitivity of these calculations to their details and to assign uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 20 publications
7
74
0
Order By: Relevance
“…15 However, the choice of cross sections is unimportant since the analysis that follows depends upon the ratios of responses to theory which, for graphite chambers, has been shown to be independent of the cross sections if a completely consistent set of cross-section data is used. 3,5 We have confirmed that the same holds true for high-Z chambers within the statistical precision considered here. Under the simulation conditions described above, the K h , K an , and K comp corrections are unity by definition.…”
Section: Iia Egsnrc Calculations Of Chamber Responsesupporting
confidence: 86%
See 3 more Smart Citations
“…15 However, the choice of cross sections is unimportant since the analysis that follows depends upon the ratios of responses to theory which, for graphite chambers, has been shown to be independent of the cross sections if a completely consistent set of cross-section data is used. 3,5 We have confirmed that the same holds true for high-Z chambers within the statistical precision considered here. Under the simulation conditions described above, the K h , K an , and K comp corrections are unity by definition.…”
Section: Iia Egsnrc Calculations Of Chamber Responsesupporting
confidence: 86%
“…3 Although these large effects likely cancel when computing values of K fl , the effects of both the density and I value on K fl were examined at the level of statistical uncertainty considered here. Figure 9 shows calculations of K fl for the plane-parallel graphite chamber as a function of the density of the graphite wall.…”
Section: Iiih1 Effect Of Density and Mean Ionization Energy On K Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Monte Carlo simulation using the EGSnrc user code cavity.cpp (version 1.41) (Ref. 12) was chosen for this task, since it has been shown by Rogers and Kawrakow 13 that EGSnrc is well suited for making…”
Section: Iiia a Wall Determination Using Egsnrcmentioning
confidence: 99%